Foreign Language Anxiety and Its Impacts on Students’ Speaking Competency - Kathreen B. Aguila; Ignatius Harjanto (ANIMA Indonesian Psychological Journal, 2016)
Anxiety may either have negative or positive impacts on one’s learning process. It is possible that anxiety may deteriorate the quality of learning process by making the learner intellectually and psychologically disturbed. In other cases, anxiety may increase students’ learning motivation due to the feeling of pressure. This study aimed to investigate the factors that contribute to students’ foreign language anxiety and its impacts on their speaking competency. The participants are university students taking English Conversation Class. Classroom observations were done to evaluate students’ speaking performance. Other instruments were Foreign Language Class Anxiety Scale (FLCAS) questionnaire and interviews. The results showed that the students had slightly high anxiety level; and there was an invert relationship between the anxiety level and the speaking scores. Several major factors that cause anxiety among the students have been identified, and it was also seen that anxiety has its most negative impacts on students’ communicative and interactive ability.